TIAA-CREF. (A), A pension giant takes a hard look at serving the customer - Rosenthal, Jean W., 1945-; Elias, Jaan; Sudhir, K.; Podolny, Joel M. (Joel Marc) ([London] : SAGE, 2016)
Founded as TIAA in 1918 to help academics avoid poverty after retirement, TIAA-CREF had grown to a Fortune 100 company, managing over $260 billion in assets for 3.2 million participants. However, for a company with so many assets and so many individual customers, TIAA-CREF was not well known. This case examines Herb Allison's attempts to diversify the company beyond its primary products.
Originally Published in: Rosenthal, J.W., Elias, J., Sudhir, K., & Podolny, J. (2006). TIAA-CREF (A): A Pension Giant Takes a Hard Look at Serving the Customer (revised 08/09/2008). 06-015. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Teachers Insurance and Annuity Association; Financial services industry -- Management -- Case studies; Customer relations -- Management -- Case studies; Customer services -- Case studies